Altered Liver Enzyme Markers in Patients with Asymptomatic, and Mild Omicron Infection: A Retrospective Study - Cao X; Xie YL; Yi JY; Liu ZL; Han M; Duan JH; Gao Q; Mu H; Zhou CL (Dove Medical Press, 2024)
Xi Cao,1 Yong-Li Xie,2,3 Jian-Ying Yi,1 Zhi-Li Liu,4 Meng Han,1 Ji-hui Duan,1 Qiang Gao,1 Hong Mu,1 Chun-lei Zhou1 1Department of Clinical Laboratory, Tianjin First Central Hospital, Tianjin, People's Republic of China; 2Department of Clinical Laboratory, Tianjin Stomatological Hospital, School of Medicine, Nankai University, Tianjin, People's Republic of China; 3Tianjin Key Laboratory of Oral and Maxillofacial Function Reconstruction, Tianjin, People's Republic of China; 4Department of Clinical Laboratory, the Third Central Hospital, Tianjin, People's Republic of ChinaCorrespondence: Hong Mu; Chun-lei Zhou, Department of Clinical Laboratory, Tianjin First Central Hospital, Tianjin, People's Republic of China, Email mutjyzxyy@163.com; tj_zcl@hotmail.comPurpose: The emergence of the SARS-CoV-2 Omicron variant has posed a significant global public health challenge. Elucidating the laboratory profiles of individuals infected with this variant is crucial for assessing organ damage. This study aimed to investigate the variations in liver function tests and their correlation with demographic characteristics and inflammatory markers in patients with early Omicron variant infections.Patients and Methods: A retrospective cohort study was conducted on 1133 mild or asymptomatic COVID-19 cases at Tianjin First Central Hospital. Data on age, gender, body mass index (BMI), and serum markers were collected and analyzed. Statistical analyses were performed using SPSS software, version 24.0.Results: Abnormal liver function parameters, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), and total bilirubin (TBIL), were observed in 314 (27.71%) patients. "Hepatocellular type" was identified in 56 (4.94%) patients, "cholestatic type" in 185 (16.33%) patients, and "mixed type" in 73 (6.44%) patients. In the mixed group, we observed a pronounced elevation in the levels of ALT, AST, and GGT. Moreover, the hepatocellular group exhibited a statistically significant increase in AST and ALT concentrations relative to both the normal and cholestatic groups. Notably, the cholestatic group demonstrated a substantial increment in ALP levels. Males had a significantly higher prevalence of "abnormal liver enzyme markers" compared to females. Patients with "abnormal liver enzyme markers" exhibited significantly decreased immunoglobulin G (IgG) levels and elevated levels of inflammatory markers, including procalcitonin (PCT), interleukin-6 (IL6), as well as C-reactive protein (CRP) compared to normal group. Logistic regression analysis revealed that male gender and PCT levels were significantly associated with the risk of abnormal liver enzyme markers. Patients in hepatocellular group were likely accompanied with high CRP levels, whereas those in the cholestatic type were associated with high IL6 levels.Conclusion: Early Omicron infection might cause liver stress response. Elevated liver enzyme marker levels were correlated with age, gender, inflammatory factors, and IgG.Keywords: Omicron variant, "abnormal liver enzyme markers", male, inflammatory markers